Digital Technology Adoption by Smallholder Farmers in Indonesia - Muhammad Hasyim (Journal of Agribusiness and Natural Resources, 2025)
Digital transformation in the agricultural sector offers significant opportunities to enhance the productivity, efficiency, and welfare of smallholder farmers in Indonesia. Nevertheless, the rate of digital technology adoption among smallholder farmers remains relatively low due to limited digital literacy, infrastructure access, economic risks, and suboptimal institutional support. This study aims to develop a more comprehensive conceptual framework to explain the dynamics of digital technology adoption by smallholder farmers in Indonesia. The research employs a qualitative approach with a conceptual paper design through a systematic conceptual review of relevant international and national literature, alongside a synthesis of key theories including Diffusion of Innovation (DOI), Technology Acceptance Model (TAM), and Unified Theory of Acceptance and Use of Technology (UTAUT). The analytical findings indicate that digital technology adoption is a multidimensional socio-technical process involving the interaction of individual cognitive capacity, household economic stability, community social capital, digital infrastructure readiness, and policy and institutional support. Based on theoretical integration and cross-country empirical findings from developing nations, this study develops the Adaptive Socio-Technical Agrarian Digitalization (ASTAD) model, which emphasizes a dynamic adaptive process within the agrarian ecosystem. This model extends classical approaches by incorporating variables such as economic risk buffer capacity, digital learning elasticity, collective trust, digital access stability, and market integration. The contribution of this research lies in reinforcing a systemic perspective for understanding smallholder agricultural digitalization in Indonesia, along with policy implications for promoting an inclusive and sustainable digital ecosystem.